Experimental analysis of the lift force on bubbles in a swarm - Kulkarni, Amol A. (Chemical Engineering Science, 2008)
The lift force acting on bubbles in a swarm has been estimated by analyzing the instantaneous velocity-time data obtained using LDA in a cylindrical bubble column. Phase distinction was achieved through the multiresolution analysis of the velocity-time data. Several important issues related to the transverse motion of bubbles subjected to a shear field have been discussed quantitatively. The actually measured bubble sizes, the respective slip velocity values in transverse and axial directions and the local shear rates (gamma) enabled the verification of known formulations for the lift coefficient (C-L) for bubbles. At many locations in the column the radial flux of the gas phase by turbulent dispersion and the radial slip were estimated. The radially inward movement of bubbles from low to high axial velocity (from column wall to center, i.e., C-L < 0) was observed at most of the measurement locations. The local lift coefficient was estimated using the transverse drag force and the values support the results from the material balance approach. The estimated C-L values showed a wide variation over the column cross-section. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Bubble; Bubble column; bubble size; hydrodynamics; LDA; lift force

Evaluation of multipoint dosing strategy in a miniaturized tubular reactor: nitration of salicylic acid - Debnath, Soujoy; Kienle, Achim; Kulkarni, Amol A. (Chemical Engineering & Technology, 2014)
A 2D non-isothermal reaction engineering model for a tubular reactor was developed for a complex reaction network of salicylic acid nitration. The influence of different operating and design parameters was studied to minimize the amount of secondary nitration products and limit the maximum temperature inside the reactor. Critical temperature effects were observed for larger reaction tubes, whereas close to isothermal conditions were perceived in smaller tubes. With single-point dosing of both reactants, complete conversion can be achieved but formation of secondary nitration products cannot be avoided. For a given number of dosing points, a suitable combination of the operating parameters allowed to achieve complete conversion and better yield of the desired product.
Keywords: Multipoint injection; nitration; Plug-flow reactor; Salicylic acid; Tubular reactor

Effect of interfacial mass transfer on the dispersion in segmented flow in straight capillaries - Deshpande, Jaydeep B.; Kulkarni, Amol A. (AICHE Journal, 2015)
The effect of interfacial mass transfer on the extent of dispersion in liquid-liquid segmented flow in straight capillaries is studied. In the absence of interfacial mass transfer, dispersion coefficient was seen to go through a minimum with increasing flow rates. In the presence of mass transfer, physicochemical properties of both the phases and slug lengths were seen to vary along the capillary length. The extent of dispersion was always higher in the presence of interfacial mass transfer. The predictions using axial dispersion model deviated noticeably for larger capillaries as the model does not account for varying buoyancy, dynamic contacting, and Marangoni convection. Simulations of a first-order interfacial reaction considering varying slug lengths showed a significant change in optimum operating parameters than the conventional approach. A special case of drop-on-demand type of controlled two-phase flow in capillaries was also studied. (c) 2015 American Institute of Chemical Engineers.
Keywords: capillary; dispersion; interfacial mass transfer; segmented flow; slugs

Effect of number of branches on the performance of fractal impeller in a stirred tank: mixing and hydrodynamics - Mule, Gunwant M.; Lohia, Rajat; Kulkarni, Amol A. (Chemical Engineering Research & Design, 2016)
Number of blades of an impeller, impeller design and its positioning in a stirred tank is known to affect the mixing in a stirred tank reactor. The extent of non-uniformity in mixing from conventional impellers can be reduced significantly using a space-filling impeller like a fractal impeller. In this work, we report the effect of number of branches (and hence the number of blades) of fractal impeller on power consumption, mixing and hydrodynamics. Velocity measurements were carried out using ultrasonic velocity profiler (UVP). Measurements showed that the performance of fractal impeller with different configuration is equivalent, however, better than standard impellers in terms of mixing achieved per unit power consumption. No significant difference was observed in radial and axial mean velocity profiles for three different configurations. However, the tangential velocity was found higher for four branches than two and three branches FL Two distinct circulation loops were observed in upper as well as lower half of the vessel in r-z plane. Strong tangential flow throughout the baffled vessel helps to achieve good mixing even at low rotational speeds. (C) 2016 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Fractal impeller; Number of branches; UVP; Tangential velocity; Mixing

Effect of physical properties of dispersed phase on the residence time distribution in straight capillaries - Raval, Joy; Suryawanshi, Nalinee B.; Kulkarni, Amol A. (Chemical Engineering Science, 2020)

Efficient processing of reactions involving diazonium salts: meerwein arylation in an impinging-jet reactor - Shukla, Chinmay A.; Atapalkar, Ranjit S.; Kulkarni, Amol A. (Organic Process Research & Development, 2020)
This work reports a novel approach for performing high-throughput synthesis of Meerwein arylation in an impingingjet reactor. The multistep reaction was performed in a single reactor via in situ diazonium salt generation followed by Meerwein arylation. The work involves many iterations between experiments and simulations (where we integrate simulating the flow, heat transfer, and reaction simultaneously) for optimization of conditions in an inverted impinging-jet reactor. The effect of design variables viz. catalyst concentration, inlet temperature, and monomer mole ratio on the yield of the desired product was studied in detail, and the simulation results were used to plan the continuous experiments. An infrared camera was used to monitor the transient reactor temperature for steady-state analysis. The lab-scale inverted impinging-jet reactor with over 93% isolated yield can offer a space-time yield of 277.78 tons/m(3)/day. The numbering-up of an inverted impinging-jet reactor can be an effective way for cleaner production of products through typical Meerwein arylation.
Keywords: computational fluid dynamics; high throughput synthesis; impinging-jet reactor; IR camera; Meerwein arylation; Numbering-up

Effect of object shape on the flow past microstructures in small channel - Mule, Gunwant M.; Kulkarni, Amol A. (Fluid Dynamics Research, 2021)
Flow past objects in microfluidics and microscale devices are used to perturb the flow and thereby achieve effective mixing and heat transfer. This paper presents the observations on the flow past bluff (elliptical, rectangular and triangular) cylindrical micropillars (objects) having different cross-sectional area in a micro-channel through 2D simulations. The pertinent range of Re based on object dimension (0.1 Re 150) was chosen to understand the wake dynamics that would remain relevant for comparison with literature data. Drag coefficient, recirculation region, critical Reynolds number for flow oscillations and vortex strength in a channel were studied. The drag coefficient was found to increase with aspect ratio of the object. The critical Re for flow oscillations was found to increase with the cross-sectional area of the object. The vortex strength in a channel was seen highest for triangular cylinder compared to elliptical and rectangular cylinder.
Keywords: 2D simulations; flow past objects; micro and mini-channels; micropillars; wake dynamics

Effect of wettability on hydrodynamics and mass transfer in small capillaries - Sampat, Chaitanya; Pal, Sayan; Kulkarni, Amol A. (Chemical Engineering Research & Design, 2021)
The wettability of the reactor wall has a significant effect on the interfacial liquid?liquid mass transfer rates in segmented flow. This work quantitatively demonstrates the importance of choosing the right material of construction of flow reactors to achieve the desired mass transfer performance. Glass and PTFE capillaries of identical diameter were used to study the effect of hydrophilic and hydrophobic surfaces on the hydrodynamics and mass transfer of the system. It was observed that for the overall mass transfer coefficient (kLa) changed by two orders of magnitude depending on the wettability of the continuous phase. The observations indicated that it is essential to achieve complete wetting of the capillary walls by the continuous phase for significant mass transfer enhancement. The observations are discussed on the basis of film thickness and slip velocity at the wall as well as the slip velocity at liquid?liquid interface. Predictions of the mass transfer coefficient using a model based on the interfacial and fluid properties showed excellent match with the experiments thereby allowing us to explore the effects of wettability on the overall mass transfer coefficient in greater detail. ? 2021 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Liquid?liquid slug flow; Mass transfer; Slip velocity; Wettability

Estimation of reaction kinetics for aromatic and heterocycles nitration in mixed acids through computational chemistry approach - Jadhav, Pandurang M.; Pandey, Raj K.; Kulkarni, Amol A. (International Journal of Chemical Kinetics, 2021)
Nitration of aromatic compounds and heterocycles in mixed acid environment is one of the regularly performed large-scale reactions in the chemical industry. Although the reaction mechanism of nitration of aromatics in mixed acid is well established, the development of a methodology for the evaluation of kinetics of exothermic aromatic nitrations in a simplified and accurate way is necessary. Here we evaluate the applicability of a kinetic evaluation methodology based on Hammett's acidity function, acidity function, and empirical activity coefficient for the nitration reaction. The contributions from the functional groups on the aromatic ring and quantitative structure-activity relationships technique are considered for these evaluations. Natural bond orbital and magnetic index nucleus independent chemical shift analyses were carried out to obtain the substitution constants. The rate constant and activation energy values were evaluated at various temperatures and sulfuric acid strengths. The results were validated by comparing with the experimental data from the literature for several molecules. The effect of various functional groups (viz carbonyl, carboxyl, methyl, and amine) substituted on the benzene ring was also evaluated. For a few identified substrates, the data were used for estimation of residence time needed for complete conversion in continuous stirred tank reactor and in a plug flow reactor to quantify the effect of substitution constant and strength of sulfuric acid. The approach will help select a suitable reactor.
Keywords: Aromatic nitration; computational chemistry; Hammett analogy; mixed acids; Reaction kinetics; reactor selection

Evaluating suitability of confined impinging jet reactor for exothermic reactions: hydrodynamics, residence time distribution, and heat transfer - Khan, Muzammilanwar S.; Mane, Mayur; Kulkarni, Amol A. (AICHE Journal, 2022)
Effect of confinement (wall proximity) of a confined impinging jet reactor (CIJR) on the flow field, residence time distribution and heat transfer are explored, through experiments and CFD simulations. Hydrodynamic characteristics are evaluated for different parameters namely confinement, impinging jet velocity, temperature gradient, and so on. For 2 mm confinement, highest values of dispersion number and overall heat transfer coefficient are observed due to interaction of turbulent eddies followed by the effect of reactor wall proximity. For the CIJR having confinements above 10 mm, jet velocity need to be greater than 3 m/s to achieve both, excellent mixing efficiency and high heat removal rate. Empirical correlations for Dispersion and Nusselt numbers as a function of Re-j and L/D are obtained, over a range of 500 <= Rej <= 3000\$\$ 500\textbackslashle {\textbackslashmathit{\textbackslashoperatornameRe}}_j\text backslashle 3000 \$\$ and 5 <= L/D <= 35\$\$ 5\textbackslashle L/D\textbackslashle 35 \$\$, which correspond to jet velocity of 0.5-3 m/s. The present study gives a basis for designing CIJR suitable for rapid, homogeneous, exothermic reactions.
Keywords: confinement; exothermic reactions; heat transfer; impinging jets; residence time distribution

Effect of microwave heating on the residence time distribution in a tubular reactor - Sonawane, Jayesh R.; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2023)
Microwave(MW) heating has been revolutionary in various applications,including chemical synthesis. A nonconventional heating approach reducesthe reaction time significantly. For a continuous flow tubular reactorunder microwaves, the temperature would change from the inlet to theoutlet depending on the dielectric constant of the reaction mass,which would further change the physical properties, viz., the densityand viscosity of the material. Such changes in the physical propertieswould lead to nonideal flows and would affect the conversion as wellas selectivity for reactions. In order to understand the extent ofsuch a nonideality, here for the first time we have done systematicstudies of the residence time distribution in a helical coil reactor.The axial dispersion model has been modified to take into accountthe temperature-dependent physical properties of the fluid. The empiricalcorrelation for the dispersion number is obtained over the range of450 & LE; P (W) & LE; 1200 and 60 & LE; T (& DEG;C) & LE; 150. This study will help model thereaction kinetics as well as reactor design under microwave specificallyfor heat sensitive reactions where variations in the overall residencetime would affect the yield and selectivity of the end product.

Experimental and kinetic modelling studies for the design of fixed bed methanol reactor over CuZA catalyst - Bagwan, Farahanaz M.; Dongapure, Pavan; Kulkarni, Amol A.; Vasireddy, Satyam Naidu (Chemical Engineering Research Design, 2024)
Direct conversion of CO 2 via hydrogenation to value-added chemicals is a vital approach for utilising CO 2 emitted into the atmosphere. In this paper, a critical analysis of reaction kinetic modelling studies is explored in a fixed bed reactor to improve methanol yield for different H 2 to CO 2 ratios by simulating a lab-scale reactor for adiabatic and isothermal conditions. The feed inlet temperature and pressure variations are applied to study the effect of both configurations on methanol production. The results show that the isothermal configuration yields 2.76% more methanol yield compared to the adiabatic reactor. The effect of H 2 to CO 2 molar ratios of 3, 6 and 9 on the performance of the catalyst and the influence of CO and CO 2 hydrogenation is investigated with model simulations. The overall methanol yield is increased from 19.03% to 36.41% with increase in H 2 to CO 2 molar ratio from 3 to 9. Experiments are performed using commercial copper-based catalyst for different temperatures of 210, 230 and 250 degrees C at a pressure of 40 bar for H 2 /CO 2 of 3 and GHSV of 720 h -1 as well as at optimal temperature of 250 degrees C and 50 bar with varying H 2 /CO 2 of 3, 6, 9 for 3 g and 6 g catalyst. The maximum methanol yield of 2.53% and space time yield of 13.59 mg/g cat .h is obtained at H 2 /CO 2 ratio of 9.
Keywords: CO2 conversion; CuZA catalyst; H2 toCO2 molar ratio; Kinetic modelling; Methanol